Evaluación de la calidad higiénico sanitaria de los quesillos expendidos en las ferias libres de la ciudad de Loja - Guarnizo Carrión, Angela Michelle (2023)
Artisanal quesillo is a highly consumed product in Ecuador for its nutritional value, so it must be free of pathogenic microorganisms since their presence can pose risks to public health. It is essential to guarantee that the production process complies with strict hygiene and quality control standards from milk collection to final packaging, ensuring that the quesillo maintains its nutritional quality and safety for consumption. This study evaluated the hygienic and sanitary quality of the quesillos sold in the free fairs of the city of Loja, following INEN 1338 standards. Microbiological cultures showed the total absence of Staphylococcus aureus, Escherichia coli, and Salmonella spp. However, enterobacteria had a high count, exceeding the limits established by the regulations. In addition, we detected the presence of other microorganisms such as coagulase- negative Staphylococcus, Streptococcus spp, Micrococcus spp, Citrobacter spp, E. aerogenes, and Y. enterocolitis. The evaluation of the associated variables revealed that personnel hygiene and incorrect use of gloves, caps, and aprons are directly related to the presence of Enterobacteriaceae.